ENCOURAGING ACADEMIC INTEGRITY BY PROVIDING E-ASSESSMENT DURING COVID-19 PANDEMIC - Sariasih, Wiwit; Latifah, Latifah (TELL - US JOURNAL, 2022)
Covid-19 pandemic has struck the world and coerce the people to work and study from home. The impact of the pandemic has caused the public services including schools, colleges and universities to apply online learning. The assessment for and of the learning would also be conducted online. E-assessment can be provided to the students using several tools such as web-based assessment, social media, blog, etc. However, it is prone to the academic misconduct or academic dishonesty. Thus, it is very urgent to advocate academic integrity to students in doing the e-learning and e-assessment. Therefore, this study aimed to investigate e-assessment that was used by the lecturers and how the lecturers encourages students to perform academic integrity in doing the e-assessment task. The study was conducted using descriptive-survey research where the sample was the English literature department of Universitas Pamulang. The strategies of conducting this study were; searching for related literature and related studies, designing the instrument based on the theory of e-assessment and academic integrity, collecting the data through the questionnaire, and interviewing and analyzing the data using descriptive statistic and narrative. The finding were; 1) there were two types of e-assessment used by the lecturer; discussion forum and multiple-choice questions. 2) The lecturer encouraged their students to conduct academic integrity by giving positive feedback for those who conducted academic integrity and building good communication and motivation to students.